(untitled) (Andamios, Revista de Investigación Social, 2009)
Rational Choice Theory, or Theory of Interpersonal Decisions, has a particular importance in contemporary political sciences, which is growing as the theory evolves and involves new methods and perspectives. But very often this theory is ignored from south of the Río Grande. This essay underlines its dynamism and makes a call to assimilate it critically.